Ciamik: accounting system application to support the realization of digitalization MSMEs / Annisa Fidanta Shafir ... [et al.] - Shafir, Annisa Fidanta; Maulana, Rizky; Hanggarjati, Mi’atu Najiata; Afif, Sultan Athaya; Pradina, Piki Rahmah (2024)
Micro, Small, and Medium Enterprises (MSMEs) are enterprises or businesses carried out by individuals, groups, small business entities, and households. Indonesia, as a developing country, makes MSMEs the main foundation of the community's economic sector. This is done to encourage the ability to develop independence in society, especially in the economic sector. There are certain criteria by which a business can be said to be an MSME. In general, the problems that occur in MSMEs, especially those included in micro and small businesses, are difficulties in preparing standard financial reports and a lack of business financial management skills. This problem occurs because MSME players still lack understanding about financial reports and consider them to be something complicated. To address these problems, we aim to design a simplified accounting system application for MSMEs and make it easy to operate the accounting system and analyze the resulting financial reports. This simple accounting system application will certainly make it easier for MSMEs to prepare financial reports, which are expected to provide enhanced accurate information in business development, financial report analysis, and financial management for MSMEs.